Synthesis and some of the electrical properties of the polymer Mosul poly Berrol - Baghdad Science Journal (مجلة بغداد للعلوم)
Thin films were prepared from poly Berrol way Ketrrukemaaih pole of platinum concentrations both Albaarol and salt in the electrolytic Alastontrel using positive effort of 7 volts on the pole and the electrical wiring of the membrane record